19.2k views
2 votes
Please show work

1. y = -2x
y = -4x + 10


2. y = 3 x
y = zx - 7


3. y = 6x + 22
y = -8

User Andy Ho
by
6.9k points

1 Answer

4 votes

(1)

since both equations express y in terms of x, equate the right sides

- 2x = - 4x + 10 ( subtract 4x from both sides )

2x = 10 ( divide both sides by 2 )

x = 5

substitute x = 5 into y = - 2x → y = - 10

solution is : (x, y ) → (5, - 10 )

(2)

equate the right sides of both equations

3x = 2x - 7 ( subtract 2x from both sides )

x = - 7

substitute x = - 7 into y = 3x → y = - 21

solution is : (x, y) → (- 7, - 21)

(3)

substitute y = - 8 into the other equation

- 8 = 6x + 22 ( subtract 22 from both sides )

- 30 = 6x ( divide both sides by 6 )

x = - 5

solution is : (x, y ) → (- 5, - 8 )



User Moli
by
5.8k points